2021
DOI: 10.1242/jcs.258601
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 inducible microRNAs sustain colon cancer by targeting multiple DNA damage response pathway factors

Abstract: Meta-analysis of transcripts in colon adenocarcinoma patient tissues led to the identification of a DNA damage responsive miR signature called DNA damage sensitive miRs (DDSMs). DDSMs were experimentally validated in the cancerous colon tissues obtained from an independent cohort of colon cancer patients and in multiple cellular systems with high levels of endogenous DNA damage. All the tested DDSMs were transcriptionally upregulated by a common intestine-specific transcription factor, CDX2. Reciprocally, DDSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…53 Another study showed that treatment with specific miR inhibitors in colon cancer reduced the high level of endogenous DNA damage sensitive miRs (DDSMs), increasing CHEK1 transcription level, which revealed the inhibitory effect of CHEK1 on colon cancer. 54 We found a novel miRNA signature risk score and analyzed its predictive effect on the prognosis of colon cancer. We have no conditions to collect our own clinical data to verify our model, which is a limitation of our study.…”
mentioning
confidence: 99%
“…53 Another study showed that treatment with specific miR inhibitors in colon cancer reduced the high level of endogenous DNA damage sensitive miRs (DDSMs), increasing CHEK1 transcription level, which revealed the inhibitory effect of CHEK1 on colon cancer. 54 We found a novel miRNA signature risk score and analyzed its predictive effect on the prognosis of colon cancer. We have no conditions to collect our own clinical data to verify our model, which is a limitation of our study.…”
mentioning
confidence: 99%
“…For experiments involving the shutdown of MRP2, BLM, or RAD54 in HCT116 WT IC60CPT R cells, cells were injected for tumor formation in mice. TAC6 polymermediated delivery of siControl, siMRP2, siBLM, and siRAD54 was carried out in the mice bearing 50 mm 3 tumors as described earlier (39). The delivery of the siRNAs (200 ng of siRNA per dose) was done every alternate day 4 times until the mice were sacrificed 21 days after initiation of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Group 2 and 3 mice were treated with 50 µL of 200 ng of siRNA complexed with TAC6 polymer (siRNA: TAC6 polymer; 1:10) at the tumor site. A total of 6 doses were given at an interval of every two day (63, 64). At the end of the experiment tumor was excised and stored at −80° C for further analysis.…”
Section: Methodsmentioning
confidence: 99%